Short proofs of some extremal results III. Issue 4 (30th August 2020) - Conlon, David; Fox, Jacob; Sudakov, Benny
Abstract : We prove a selection of results from different areas of extremal combinatorics, including complete or partial solutions to a number of open problems. These results, coming mainly from extremal graph theory and Ramsey theory, have been collected together because in each case the relevant proofs are reasonably short.